Pengaruh Hospitality Personel Pengamanan Penerbangan (AVSEC) Terhadap Kepuasan Penumpang Bandar Udara Internasional Minangkabau - Indah Tri Kusumastuti; Dwi Afriyanto; Alwazir Abdusshomad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The aspect of hospitality service at airports is very important to create a safe and comfortable travel experience. Minangkabau International Airport has experienced an increase in the number of passengers, so the quality of service, especially by security personnel, needs to be improved. However, there are still complaints from passengers regarding the unprofessional and non-responsive attitudes of the personnel. In fact, these interactions play a crucial role in shaping passengers' perceptions. This research uses a quantitative method with purposive sampling technique. The data were analyzed using SPSS 25 to see the impact of hospitality service by security personnel on passenger satisfaction. The results show that good service significantly increases passenger satisfaction, with a contribution of 49%. The significance value < 0.05 proves a positive influence between the two variables. This finding emphasizes that the hospitality aspect of security personnel plays an important role in enhancing passenger satisfaction. However, consistent and fair treatment still needs to be improved. Some suggested improvements include human resources training, enhancement of the complaint system, addition of hospitality aspects in SOPs, monitoring and evaluation programs, as well as further research.